1999
DOI: 10.1007/s003000050365
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study on digestive processes in the Antarctic krill, Euphausia superba , with special regard to chitinolytic enzymes

Abstract: Feeding experiments of 9, 14 and 20 days duration were carried out on the Antarctic krill, Euphausia superba. Two groups were fed with the chitinous diatom Cyclotella cryptica and the non-chitinous green algae Dunaliella bioculata, respectively. A control group remained unfed. The time courses of the activities of endo-and exochitinase in the stomach and the midgut gland were compared with those of the digestive enzymes protease, cellulase (1,4-b-D-glucanase) and laminarinase (1,3-b-D-glucanase). Speci®c activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Because of the complex digestive process, enzyme activity may vary between the two organs (Saborowski and Buchholz 1999). We found higher digestive enzyme activity in the stomach than in the midgut gland, a difference noted previously (Buchholz 1989;Saborowski and Buchholz 1999), probably reflecting a higher concentration of digestive juice. In either organs of adult krill the laminarinase and proteinase activity was higher in autumn than in summer.…”
Section: Digestive Enzyme Activitysupporting
confidence: 56%
See 2 more Smart Citations
“…Because of the complex digestive process, enzyme activity may vary between the two organs (Saborowski and Buchholz 1999). We found higher digestive enzyme activity in the stomach than in the midgut gland, a difference noted previously (Buchholz 1989;Saborowski and Buchholz 1999), probably reflecting a higher concentration of digestive juice. In either organs of adult krill the laminarinase and proteinase activity was higher in autumn than in summer.…”
Section: Digestive Enzyme Activitysupporting
confidence: 56%
“…These findings, like our own, are suggestive of an increase in enzyme concentrations at low food levels. In contrast, Saborowski and Buchholz (1999) showed that in starving E. superba, digestive enzyme activity rapidly decreases in the stomach and to a lesser extend also in the midgut gland. However, after advanced starvation of several days, activities recovered again but did not reach initial values.…”
Section: Digestive Enzyme Activitymentioning
confidence: 85%
See 1 more Smart Citation
“…Total proteinase activity was determined by the hydrolysis of azocasein as described by GarciaCarreño (1992) and modified by Saborowski and Buchholz (1999). The reaction mixture contained 200 Al Tris-HCl (0.1 mold l À1 , pH 6.0, supplemented with 0.01 mold l À1 CaCl 2 ) and 20 Al of the midgut gland extract.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…On starvation crustaceans reduce the size of the midgut gland and metabolize storage products such as lipids and glycogen (Strus, 1987;Papathanassiou and King, 1984). Furthermore, digestive enzyme activities decrease on starvation (Saborowski and Buchholz, 1999). The regulative potential of PKII in the midgut gland seems to be a suitable mechanism to control the glycolytic energy transfer.…”
Section: Organ and Tissue Specificitymentioning
confidence: 99%